Gentrification, Charter Schools, and Enrollment Patterns in Washington, DC: Shared Growth or New Forms of Educational Inequality?. Issue 3 (26th May 2020) - Mann, Bryan; Bennett, Heather; Rogers, Annah
ABSTRACT: Cities in the United States and across the world have experienced gentrification at the same time as school choice policies have become more popular. This research examines the relationship between gentrification and charter schooling, seeking to understand how together they affect demographic composition of schools across Washington, DC. This study uses geographic information systems (GIS) mapping and statistical techniques to show that gentrified neighborhoods are more likely to have charter schools. Additionally, the demographic compositions of charter schools and traditional public schools differ depending on the gentrification classification of the census tract in which the schools are located. While a handful of diverse charter schools exist in gentrified neighborhoods and some diverse public schools exist in traditionally affluent neighborhoods, schools in Washington, DC remain racially and economically isolated overall.